The isostretching in low back pain chronic in college students. - Sousa, Paula Fernanda Batista de; Carvalho, Ramonyelle Helkys Macedo; Matos, Ludmilla Karen Brandão Lima de (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Chronic low back pain is a symptom located in the lower region of the back due to an abnormal change in this region. Among the methods to promote the relief of this symptom, the isostretching can be included, considered a global postural method. Objective: To investigate the isostretching technique on low back pain in college students. Method: The study included 10 subjects aged between 19 and 29 years. In the first stage they just met at home for a month the Low back pain Frequency Journal and in the second stage of the research they have been evaluated following items in an evaluation form, continued filling out the diary and were submitted to 15 sessions. Results: We observed significant improvement in back pain between participants during treatment with isostretching, where the average value was 6.40 ± 0.69 before treatment and 2.40 ± 0.54 was later. Regarding the 3rd finger test soil was demonstrated according to the results obtained before and after treatment increased flexibility, the average value was 17.05 ± 5.04 before treatment and after was 10 50 ± 3.97. Regarding the Schober test could be seen some improvement. Before treatment, the mean value was 15.15 ± 0.59 and 15.20 ± 0.64 was after. Conclusion: The results reported in this study show that the Isostretching method has not shown significant results in the mobility of the spine of the research participants, according to the analysis of data obtained by measuring with the Stibor and Schober tests. The method proved to be effective in improving chronic back pain and flexibility.